2017
DOI: 10.1620/tjem.241.319
|View full text |Cite
|
Sign up to set email alerts
|

Alfacalcidol Increases the Therapeutic Efficacy of Ibandronate on Bone Mineral Density in Japanese Women with Primary Osteoporosis

Abstract: Bisphosphonates (BPs) increase bone mineral density (BMD) through the inhibition of osteoclast activity. Among BPs, ibandronate (IBN) is a strong inhibitor of bone resorption. However, the effects of a vitamin D analogue, alfacalcidol (ALF), on IBN treatment for osteoporosis is unknown. Fifty-three treatment-naïve post-menopausal women with primary osteoporosis were recruited and divided into IBN-treatment group (IBN group) and IBN with ALF group (IBN/ALF group). IBN (1.0 mg) was intravenously injected once a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
(27 reference statements)
0
8
0
1
Order By: Relevance
“…On the other hand, DMAb likely increases H-BMD. 4 , 19 Eriksen et al have reviewed the effects of TPTD treatment on hip OP and concluded that TPTD showed positive effect in patients with hip OP. 20 Further, in this study, H-BMD, especially FN-BMD, was greatly increased by DMAb after pretreatment with TPTD.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, DMAb likely increases H-BMD. 4 , 19 Eriksen et al have reviewed the effects of TPTD treatment on hip OP and concluded that TPTD showed positive effect in patients with hip OP. 20 Further, in this study, H-BMD, especially FN-BMD, was greatly increased by DMAb after pretreatment with TPTD.…”
Section: Discussionmentioning
confidence: 99%
“…The coefficients of variation of the L-BMD and H-BMD measurements were 1.0% and 0.6%, respectively. 13 All TRACP-5b and BAP measurements were performed by SRL Inc. (Tokyo, Japan). Results in Table 1 – 3 were expressed as mean ± SD, and results in Figure 1 were expressed as mean ± standard error (SE).…”
Section: Methodsmentioning
confidence: 99%
“…Osteoporosis is a systemic disease characterized by decreased bone density and more risk of bone breakage. It is the most famous metabolic bone disease in the adults, especially in postmenopausal women (1) .…”
Section: Introductionmentioning
confidence: 99%